Anti-wrinkle non-ironing fabric and preparation method thereof
By grafting UV absorbers and flame retardants onto viscose fabrics and finishing them with polyurethane emulsion, wrinkle-resistant and iron-free fabrics are prepared, which solves the problems of viscose fabrics being prone to wrinkling and flammability and improves the overall performance of the fabrics.
Patent Information
- Application Number
- CN202510903141.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-01
- Publication Date
- 2025-10-24
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Viscose fabrics are prone to wrinkling and difficult to restore, and they pose a flammability risk, limiting their application.
Viscose fabric is reacted with UV absorber and flame retardant to prepare pre-modified fabric, and then reacted with polyurethane emulsion finishing liquid to form wrinkle-resistant and wrinkle-free fabric, thereby improving its wrinkle-resistant, flame-retardant and UV-resistant properties.
The wrinkle resistance, flame retardancy and UV resistance of viscose fabrics have been significantly improved, which has enhanced the safety and comfort of fabrics.
Smart Images

Figure BDA0005477755540000031 
Figure BDA0005477755540000041 
Figure BDA0005477755540000051
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of fabric, in particular to an anti-wrinkle non-iron fabric and a preparation method thereof. BACKGROUND
[0002] Viscose fabric is a textile made of viscose fiber as raw material. Viscose fabric has the following advantages: strong moisture absorption and air permeability, moisture absorption rate close to human skin demand, can quickly absorb sweat and promote evaporation, known as "breathable fabric"; skin-friendly and comfortable, soft and smooth touch, excellent antistatic performance, no sticky feeling when worn, suitable for sports wear and close-fitting clothes; good dyeing performance, easy to color and bright color, high fastness; as a regenerated fiber, the raw material comes from biomass materials (wood, bamboo, cotton lint, etc.), with little environmental pollution. Based on these advantages, viscose fabric is widely used in clothing, home textiles, medical consumables (surgical gowns, masks, gauze, etc.), industrial cloth and other fields. However, viscose fabric also has an undeniable defect, which is prone to wrinkling and difficult to recover; due to its chemical composition and fiber structure, viscose fabric still retains the disadvantage of flammability of cellulose-based fabrics, and as its use range continues to expand, the potential fire risk also increases. Therefore, it is necessary to improve the anti-wrinkle and flame-retardant properties of viscose fabric. SUMMARY
[0003] The purpose of the present application is to provide an anti-wrinkle non-iron fabric and a preparation method thereof to solve the problems in the prior art.
[0004] In order to solve the above technical problems, the present application provides the following technical scheme:
[0005] An anti-wrinkle non-iron fabric is prepared by reacting viscose fabric with an ultraviolet absorber and an epoxy chloropropane, and then reacting with a flame retardant to obtain a pre-modified fabric; an indole glycol, a polytetrahydrofuran diol, 2,2-dimethylol propionic acid, and isophorone diisocyanate are reacted, and then reacted with triethylamine to obtain a polyurethane emulsion; the polyurethane emulsion is mixed with sodium chloride to prepare an aqueous polyurethane finishing solution; the pre-modified fabric and the aqueous polyurethane finishing solution are reacted to obtain the anti-wrinkle non-iron fabric.
[0006] The ultraviolet absorber is prepared by reacting 4-(2-chloroethyl)benzaldehyde and 3,5-difluorobenzyl cyanide;
[0007] The flame retardant is prepared by reacting cyanuric chloride and [(4-aminophenyl)methylene]diphosphoric acid;
[0008] The indole glycol is prepared by reacting 3-indole formaldehyde and 3-amino-1,5-pentanediol.
[0009] A preparation method of an anti-wrinkle non-iron fabric, the preparation method of the anti-wrinkle non-iron fabric comprises the following preparation steps:
[0010] (1) Put the viscose fabric into the anti-ultraviolet finishing liquid, the bath ratio is 1:20, double-dip double-nip, the wet pick-up rate is 80%, react for 30-40 min at 50-60℃, wash 4-6 times with deionized water, dry at 100℃ for 1-2 h, immerse in the flame-retardant finishing agent, the bath ratio is 1:30, stand for 20-30 min, double-dip double-nip, the wet pick-up rate is 80%, react for 2-3 h at 70-76℃, wash 4-6 times with deionized water, dry at 100℃ for 1-2 h, prepare the pre-modified fabric;
[0011] (2) Mix indolyl glycol, polytetrahydrofuran diol and isophorone diisocyanate uniformly according to the molar ratio of 1:(2-2.2):(4.8-5.2), add 0.03-0.05 times of dibutyl tin dilaurate based on the mass of isophorone diisocyanate, stir at 80-85℃ and 100-120 r / min under nitrogen protection for 3-4 h, cool down to 55-58℃, add 0.2-0.22 times of 2,2-dimethylol propionic acid based on the molar amount of isophorone diisocyanate, continue to stir for 20-30 min, cool down to 40-42℃, add 0.7-0.8 times of triethylamine based on the mass of 2,2-dimethylol propionic acid, continue to stir for 20-30 min, cool down to room temperature, add deionized water to adjust the solid content to 40%, stir at 2000-2400 r / min for 20-30 min, prepare the polyurethane emulsion; mix the polyurethane emulsion, sodium chloride and deionized water according to the mass ratio of 1:(0.04-0.06):(3-3.4) to prepare the water-based polyurethane finishing liquid;
[0012] (3) Immerse the pre-modified fabric in the water-based polyurethane finishing liquid, the bath ratio is 1:30, double-dip double-nip at room temperature, the wet pick-up rate is 80%, pre-bake at 80℃ for 3-5 min, heat up to 150℃, bake for 4-6 min, wash 4-6 times with deionized water, dry at 100℃ for 1-2 h, prepare the anti-wrinkle non-iron fabric.
[0013] As an optimization, the areal density of the viscose fabric in step (1) is 250 g / m 2 .
[0014] As an optimization, the preparation method of the anti-ultraviolet finishing liquid in step (1) is as follows: mix the ultraviolet absorber, epichlorohydrin and anhydrous ethanol uniformly according to the mass ratio of 1:(1.2-1.4):(25-27), adjust the pH to 8-9 with sodium carbonate aqueous solution, prepare the anti-ultraviolet finishing liquid.
[0015] As optimization, the preparation method of the ultraviolet absorber is as follows: sodium hydroxide and anhydrous ethanol are mixed uniformly at a mass ratio of 1:(90-100) to prepare a sodium hydroxide alcohol solution; 4-(2-chloroethyl) benzaldehyde and 3,5-difluoro phenylacetonitrile are added to the sodium hydroxide alcohol solution in a molar ratio of 1:1, and the mass of 4-(2-chloroethyl) benzaldehyde is 24-26 times that of the sodium hydroxide alcohol solution; the mixture is stirred at 30-40°C and 200-300 r / min for 3-4 h; and the mixture is dried at 50-60°C under vacuum for 8-10 h to obtain the ultraviolet absorber; and the reaction process is as follows:
[0016]
[0017] As optimization, the mass fraction of the sodium carbonate aqueous solution is 10%.
[0018] As optimization, the preparation method of the flame-retardant finishing solution in step (1) is as follows: a flame retardant, triphenylphosphine and anhydrous ethanol are mixed uniformly at a mass ratio of 1:(0.05-0.07):(18-20) to prepare the flame-retardant finishing solution.
[0019] As optimization, the preparation method of the flame retardant is as follows: cyanuric chloride and [(4-aminophenyl) methylene] diphosphonic acid are added to toluene in a molar ratio of 1:3, and the mass of cyanuric chloride is 20-24 times that of the toluene; triethylamine is added in an amount of 0.04-0.06 times that of cyanuric chloride; the mixture is stirred at 50-60°C and 300-500 r / min for 4-5 h; and the mixture is dried at 70-80°C under vacuum for 10-12 h to obtain the flame retardant; and the reaction process is as follows:
[0020]
[0021] As optimization, the CAS number of the [(4-aminophenyl) methylene] diphosphonic acid is 613688-58-7; and the structural formula is as follows:
[0022] As optimization, the preparation method of the indolyl glycol in step (2) is as follows: 3-indolecarboxaldehyde and 3-amino-1,5-pentanediol are added to tetrahydrofuran in a molar ratio of 1:1, and the mass of 3-indolecarboxaldehyde is 15-17 times that of the tetrahydrofuran; the mixture is stirred at 60-65°C and 200-300 r / min for 5-6 h under nitrogen protection; and the mixture is dried at 60-70°C under vacuum for 12-14 h to obtain the indolyl glycol; and the reaction process is as follows:
[0023]
[0024] As optimization, the type of the polytetramethylene glycol in step (2) is PTMG2000.
[0025] Compared with the prior art, the beneficial effects achieved by the present invention are:
[0026] When preparing the wrinkle-resistant and ironing-free fabric, the present invention comprises the following steps: reacting 4-(2-chloroethyl)benzaldehyde and 3,5-difluorobenzeneacetonitrile to obtain an ultraviolet absorber; reacting cyanuric chloride and [(4-aminophenyl)methylene]diphosphoric acid to obtain a flame retardant; reacting viscose fabric with the ultraviolet absorber and epichlorohydrin, and then reacting with the flame retardant to obtain a pre-modified fabric; reacting 3-indolecarboxaldehyde and 3-amino-1,5-pentanediol to obtain indole diol; reacting indole diol, polytetrahydrofuran diol, 2,2-dihydroxymethylpropionic acid, and isophorone diisocyanate, and then reacting with triethylamine to obtain a polyurethane emulsion; preparing an aqueous polyurethane finishing liquid by mixing the polyurethane emulsion with sodium chloride; and reacting the pre-modified fabric with the aqueous polyurethane finishing liquid to obtain the wrinkle-resistant and ironing-free fabric.
[0027] First, 4-(2-chloroethyl)benzaldehyde and 3,5-difluorobenzeneacetonitrile are reacted to prepare a UV absorber, and chlorine atoms are introduced into the UV absorber; the chlorine atoms on the UV absorber and epichlorohydrin can undergo a substitution reaction with the hydroxyl groups on the viscose fabric, and the UV absorber and epoxy groups are grafted onto the viscose fabric; the UV absorber grafted onto the viscose fabric contains a diphenyl acrylonitrile structure, which can undergo a cis-trans isomerization change under ultraviolet light, from the Z configuration to the E configuration. This isomerization change is reversible and can be restored to the Z configuration after the ultraviolet light is removed. The reversible cis-trans isomerization change can absorb ultraviolet light energy and convert it into chemical energy, thereby improving the UV resistance of the wrinkle-resistant and iron-free fabric; the mechanism of action is as follows:
[0028]
[0029] A phosphorus-nitrogen synergistic flame retardant was synthesized by reacting cyanuric chloride and [(4-aminophenyl)methylene]diphosphoric acid. The phosphate groups on the flame retardant can undergo a ring-opening reaction with the epoxy groups introduced on the viscose fabric under the action of a catalyst, thereby grafting the flame retardant on the viscose fabric and improving the flame retardant properties of the wrinkle-resistant and iron-free fabric.
[0030] Secondly, 3-indole formaldehyde, 3-amino-1, 5-pentanediol are reacted to prepare indole glycol; after indole glycol, polytetrahydrofuran diol, 2, 2-dihydroxymethyl propionic acid, isophorone diisocyanate are reacted, then reacted with triethylamine to prepare a polyurethane emulsion. The polyurethane emulsion is prepared into an aqueous polyurethane finishing liquid with sodium chloride; viscose fabric is a cellulose fabric with low breaking strength and easy wrinkling; from the perspective of polymer science, the wrinkles of the fabric are caused by high-elastic deformation with very slow recovery speed and plastic deformation that cannot be recovered, and the part of deformation is related to the force between molecular segments; therefore, the idea of implementing wrinkle-resistant finishing of the fabric is to strengthen and increase the force between fiber molecules, accelerate the elastic recovery of the fiber, and improve the elasticity; the aqueous polyurethane resin has good chemical stability, small pollution, and convenient use, and has good film-forming property and elasticity, and can be used in the wrinkle-resistant finishing of viscose fabric, can rely on the resilience of the viscose fabric to improve the wrinkle-resistant performance of the viscose fabric; at the same time, the excellent tensile property of the polyurethane can improve the tensile property of the viscose fabric; the indole group introduced on the polyurethane main chain contains a conjugated aromatic structure, which can absorb ultraviolet light through the transition of π electrons, and further improve the ultraviolet resistance of the wrinkle-resistant and non-iron fabric; the indole group can also form a cation-π supramolecular interaction with sodium ions to form a "point-to-plane" non-covalent bond, so that a crosslinked network is formed between the polyurethane molecular chains, and the tensile property of the wrinkle-resistant and non-iron fabric is further improved. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present application will be clearly and completely described below with reference to the embodiments of the present application. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative labor fall within the scope of protection of the present application.
[0032] The type of polytetrahydrofuran diol used in the following examples and comparative examples is PTMG2000; the areal density of the viscose fabric used is 250 g / m 2 .
[0033] Example 1:
[0034] A preparation method of a wrinkle-resistant and non-iron fabric, the preparation method of the wrinkle-resistant and non-iron fabric comprises the following preparation steps:
[0035] (1) mixing sodium hydroxide and anhydrous ethanol uniformly according to a mass ratio of 1:90 to prepare a sodium hydroxide alcohol solution; adding 4-(2-chloroethyl)benzaldehyde and 3,5-difluorophenylacetonitrile according to a molar ratio of 1:1 into the sodium hydroxide alcohol solution with a mass of 4-(2-chloroethyl)benzaldehyde being 24 times, stirring at 30°C and 200 r / min for 4 h, drying at 50°C under vacuum for 10 h to prepare an ultraviolet absorber; adding cyanuric chloride and [(4-aminophenyl)methylene]diphosphonic acid according to a molar ratio of 1:3 into toluene with a mass of cyanuric chloride being 20 times, adding triethylamine with a mass of 0.04 times of cyanuric chloride, stirring at 50°C and 300 r / min for 5 h, and drying at 70°C under vacuum for 12 h to prepare a flame retardant;
[0036] (2) mixing the ultraviolet absorber, epichlorohydrin and anhydrous ethanol uniformly according to a mass ratio of 1:1.2:25, adjusting pH to 8 with a 10% sodium carbonate aqueous solution to prepare an anti-ultraviolet finishing liquid; mixing the flame retardant, triphenylphosphine and anhydrous ethanol uniformly according to a mass ratio of 1:0.05:18 to prepare a flame-retardant finishing liquid; placing the viscose fabric into the anti-ultraviolet finishing liquid, with a bath ratio of 1:20, double-dipping and double-rolling, a liquid retention rate of 80%, reacting at 50°C for 40 min, washing with deionized water for 4 times, drying at 100°C for 1 h, immersing in the flame-retardant finishing agent, with a bath ratio of 1:30, standing for 20 min, double-dipping and double-rolling, a liquid retention rate of 80%, reacting at 70°C for 3 h, washing with deionized water for 4 times, and drying at 100°C for 1 h to prepare a pre-modified fabric;
[0037] (3) adding 3-indole formaldehyde and 3-amino-1,5-pentanediol according to a molar ratio of 1:1 into tetrahydrofuran with a mass of 3-indole formaldehyde being 15 times, stirring at 60°C and 200 r / min for 6 h under nitrogen protection, and drying at 60°C under vacuum for 14 h to prepare an indole glycol; mixing the indole glycol, polytetrahydrofuran diol and isophorone diisocyanate according to a molar ratio of 1:2:4.8, adding dibutyltin dilaurate with a mass of 0.03 times of isophorone diisocyanate, stirring at 80°C and 100 r / min for 4 h under nitrogen protection, cooling to 55°C, adding 2,2-dimethylol propionic acid with a molar amount of 0.2 times of isophorone diisocyanate, continuing to stir for 30 min, cooling to 40°C, adding triethylamine with a mass of 0.7 times of 2,2-dimethylol propionic acid, continuing to stir for 30 min, cooling to room temperature, adding deionized water to adjust the solid content to 40%, and stirring at 2000 r / min for 30 min to prepare a polyurethane emulsion; mixing the polyurethane emulsion, sodium chloride and deionized water according to a mass ratio of 1:0.04:3 to prepare a water-based polyurethane finishing liquid;
[0038] (4) the pre-modified fabric is immersed in the water-based polyurethane finishing liquid with a bath ratio of 1:30, double-dip-double-nip is carried out at room temperature, the wet pick-up rate is 80%, pre-drying is carried out at 80℃ for 3 min, the temperature is increased to 150℃, baking is carried out for 4 min, deionized water is used for washing 4 times, and drying is carried out at 100℃ for 1 h, so as to obtain the wrinkle-resistant and non-iron fabric.
[0039] Example 2:
[0040] A preparation method of a wrinkle-resistant and non-iron fabric, the preparation method of the wrinkle-resistant and non-iron fabric comprising the following preparation steps:
[0041] (1) sodium hydroxide and anhydrous ethanol are uniformly mixed in a mass ratio of 1:95 to prepare a sodium hydroxide alcohol solution; 4-(2-chloroethyl) benzaldehyde and 3,5-difluoro phenylacetonitrile are added to the sodium hydroxide alcohol solution in a molar ratio of 1:1, and the mass of the 4-(2-chloroethyl) benzaldehyde is 25 times that of the sodium hydroxide alcohol solution; stirring is carried out at 35℃ and 250 r / min for 3.5 h; drying is carried out under vacuum conditions at 55℃ for 9 h, so as to obtain an ultraviolet absorber; cyanuric chloride and [(4-aminophenyl) methylene] diphosphoric acid are added to toluene in a molar ratio of 1:3, and the mass of the cyanuric chloride is 22 times that of the toluene; 0.05 times the mass of the cyanuric chloride is added to triethylamine; stirring is carried out at 55℃ and 400 r / min for 4.5 h; drying is carried out under vacuum conditions at 75℃ for 11 h, so as to obtain a flame retardant;
[0042] (2) the ultraviolet absorber, epichlorohydrin and anhydrous ethanol are uniformly mixed in a mass ratio of 1:1.3:26, and the pH is adjusted to 8.5 by using a 10% sodium carbonate aqueous solution to prepare an anti-ultraviolet finishing liquid; the flame retardant, triphenylphosphine and anhydrous ethanol are uniformly mixed in a mass ratio of 1:0.06:19 to prepare a flame-retardant finishing liquid; the viscose fabric is placed in the anti-ultraviolet finishing liquid, double-dip-double-nip is carried out with a bath ratio of 1:20, the wet pick-up rate is 80%, reaction is carried out at 55℃ for 35 min, deionized water is used for washing 5 times, drying is carried out at 100℃ for 1.5 h, the viscose fabric is immersed in the flame-retardant finishing agent, the bath ratio is 1:30, the viscose fabric is placed for 25 min, double-dip-double-nip is carried out with a wet pick-up rate of 80%, reaction is carried out at 73℃ for 2.5 h, deionized water is used for washing 5 times, and drying is carried out at 100℃ for 1.5 h, so as to obtain the pre-modified fabric;
[0043] (3) 3-indole carboxaldehyde, 3-amino-1,5-pentanediol were added into 3-indole carboxaldehyde mass 16 times of tetrahydrofuran in a molar ratio of 1:1, under nitrogen protection, 62.5℃, 250r / min stirring reaction 5.5h, under vacuum condition, 65℃ drying 13h, to prepare indole diol; indole diol, polytetrahydrofuran diol, isophorone diisocyanate were mixed uniformly in a molar ratio of 1:2.1:5, isophorone diisocyanate mass 0.04 times of dibutyl tin dilaurate was added, under nitrogen protection, 82.5℃, 110r / min stirring reaction 3.5h, cooling to 56.5℃, 2,2-dimethylol propionic acid of isophorone diisocyanate molar amount 0.21 times was added, continue to stir for 25min, cooling to 41℃, 2,2-dimethylol propionic acid mass 0.75 times of triethylamine was added, continue to stir for 25min, cooling to room temperature, deionized water was added to adjust the solid content to 40%, stirring at 2200r / min for 25min, to prepare polyurethane emulsion; the polyurethane emulsion, sodium chloride, deionized water were mixed in a mass ratio of 1:0.05:3.2 to prepare water-based polyurethane finishing liquid;
[0044] (4) The pre-modified fabric was immersed in the water-based polyurethane finishing liquid with a bath ratio of 1:30, and was double-immersed and double-nipped at room temperature with a wet rate of 80%. The fabric was pre-baked at 80℃ for 4min, heated to 150℃, and baked for 5min. The fabric was washed with deionized water for 5 times and dried at 100℃ for 1.5h to obtain the wrinkle-resistant and non-iron fabric.
[0045] Example 3:
[0046] A preparation method of a wrinkle-resistant and non-iron fabric, the preparation method of the wrinkle-resistant and non-iron fabric comprising the following preparation steps:
[0047] (1) Sodium hydroxide and anhydrous ethanol were mixed uniformly in a mass ratio of 1:100 to prepare a sodium hydroxide alcohol solution; 4-(2-chloroethyl) benzaldehyde and 3,5-difluorobenzyl cyanide were added into 4-(2-chloroethyl) benzaldehyde mass 26 times of the sodium hydroxide alcohol solution in a molar ratio of 1:1, stirring at 40℃, 300r / min for 3h, drying at 60℃ under vacuum condition for 8h to prepare an ultraviolet absorber; cyanuric chloride and [(4-aminophenyl) methylene] diphosphoric acid were added into cyanuric chloride mass 24 times of toluene in a molar ratio of 1:3, cyanuric chloride mass 0.06 times of triethylamine was added, stirring at 60℃, 500r / min for 4h, drying at 80℃ under vacuum condition for 10h to prepare a flame retardant;
[0048] (2) The ultraviolet absorber, epichlorohydrin, and anhydrous ethanol are mixed uniformly in a mass ratio of 1:1.4:27, and a 10% sodium carbonate aqueous solution is used to adjust the pH to 9 to prepare an anti-ultraviolet finishing liquid; the flame retardant, triphenylphosphine, and anhydrous ethanol are mixed uniformly in a mass ratio of 1:0.07:20 to prepare a flame-retardant finishing liquid; the viscose fabric is placed in the anti-ultraviolet finishing liquid, the bath ratio is 1:20, two-dip-two-pad is performed, the liquid retention rate is 80%, reaction is performed at 60°C for 30 min, washing is performed 6 times with deionized water, drying is performed at 100°C for 2 h, the fabric is immersed in the flame-retardant finishing agent, the bath ratio is 1:30, standing is performed for 30 min, two-dip-two-pad is performed, the liquid retention rate is 80%, reaction is performed at 76°C for 2 h, washing is performed 6 times with deionized water, drying is performed at 100°C for 2 h, and a pre-modified fabric is prepared;
[0049] (3) 3-indole formaldehyde and 3-amino-1,5-pentanediol are added to 3-indole formaldehyde in an amount of 17 times of the mass of the 3-indole formaldehyde in tetrahydrofuran, stirring is performed at 65°C and 300 r / min under nitrogen protection for 5 h, drying is performed at 70°C under vacuum for 12 h, and an indole glycol is prepared; the indole glycol, polytetrahydrofuran diol, and isophorone diisocyanate are mixed uniformly in a molar ratio of 1:2.2:5.2, dibutyltin dilaurate in an amount of 0.05 times of the mass of the isophorone diisocyanate is added, stirring is performed at 85°C and 120 r / min under nitrogen protection for 3 h, 2,2-dimethylol propionic acid in an amount of 0.22 times of the molar amount of the isophorone diisocyanate is added after the temperature is lowered to 58°C, stirring is continued for 20 min, triethylamine in an amount of 0.8 times of the mass of the 2,2-dimethylol propionic acid is added after the temperature is lowered to 42°C, stirring is continued for 20 min, the temperature is lowered to room temperature, deionized water is added to adjust the solid content to 40%, and stirring is performed at 2400 r / min for 20 min, and a polyurethane emulsion is prepared; the polyurethane emulsion, sodium chloride, and deionized water are mixed in a mass ratio of 1:0.06:3.4 to prepare a water-based polyurethane finishing liquid;
[0050] (4) The pre-modified fabric is immersed in the water-based polyurethane finishing liquid, two-dip-two-pad is performed at room temperature, the liquid retention rate is 80%, pre-baking is performed at 80°C for 5 min, the temperature is raised to 150°C, baking is performed for 6 min, washing is performed 6 times with deionized water, drying is performed at 100°C for 2 h, and a wrinkle-resistant non-iron fabric is prepared.
[0051] Comparative Example 1
[0052] The preparation method of the wrinkle-resistant non-iron fabric of Comparative Example 1 is different from that of Example 2 in steps (1) and (2). Step (1) is modified as follows: cyanuric chloride, [(4-aminophenyl)methylene]diphosphonic acid are added in a molar ratio of 1:3 to 22 times the mass of cyanuric chloride in toluene, 0.05 times the mass of cyanuric chloride in triethylamine is added, stirring is carried out at 55°C and 400 r / min for 4.5 h, and drying is carried out under vacuum at 75°C for 11 h to prepare a flame retardant; step (2) is modified as follows: 1-chlorobutane, epichlorohydrin, and anhydrous ethanol are mixed in a mass ratio of 1:1.4:27, a 10% sodium carbonate aqueous solution is used to adjust the pH to 9 to prepare an anti-ultraviolet finishing solution; the flame retardant, triphenylphosphine, and anhydrous ethanol are mixed in a mass ratio of 1:0.07:20 to prepare a flame-retardant finishing solution; the viscose fabric is placed in the anti-ultraviolet finishing solution, the bath ratio is 1:20, double-dip double-nip is carried out, the liquid retention rate is 80%, reaction is carried out at 60°C for 30 min, washing is carried out 6 times with deionized water, drying is carried out at 100°C for 2 h, the fabric is immersed in the flame-retardant finishing solution, the bath ratio is 1:30, standing is carried out for 30 min, double-dip double-nip is carried out, the liquid retention rate is 80%, reaction is carried out at 76°C for 2 h, washing is carried out 6 times with deionized water, and drying is carried out at 100°C for 2 h to prepare a pre-modified fabric. The remaining steps are the same as in Example 2.
[0053] Comparative Example 2:
[0054] The preparation method of the wrinkle-resistant non-iron fabric of Comparative Example 2 is different from that of Example 2 in steps (1) and (2). Step (1) is modified as follows: (1) sodium hydroxide and anhydrous ethanol are mixed in a mass ratio of 1:95 to prepare a sodium hydroxide alcohol solution; 4-(2-chloroethyl)benzaldehyde and 3,5-difluorobenzyl cyanide are added in a molar ratio of 1:1 to 25 times the mass of 4-(2-chloroethyl)benzaldehyde in the sodium hydroxide alcohol solution, stirring is carried out at 35°C and 250 r / min for 3.5 h, and drying is carried out under vacuum at 55°C for 9 h to prepare an ultraviolet absorber; step (2) is modified as follows: the ultraviolet absorber, epichlorohydrin, and anhydrous ethanol are mixed in a mass ratio of 1:1.3:26, a 10% sodium carbonate aqueous solution is used to adjust the pH to 8.5 to prepare an anti-ultraviolet finishing solution; the viscose fabric is placed in the anti-ultraviolet finishing solution, the bath ratio is 1:20, double-dip double-nip is carried out, the liquid retention rate is 80%, reaction is carried out at 55°C for 35 min, washing is carried out 5 times with deionized water, drying is carried out at 100°C for 1.5 h, and a pre-modified fabric is prepared. The remaining steps are the same as in Example 2.
[0055] Comparative Example 3:
[0056] The preparation method of the anti-wrinkle non-iron fabric of Comparative Example 3 is different from that of Example 2 only in step (3), which is modified as follows: 1,5-pentanediol, polytetrahydrofuran diol and isophorone diisocyanate are uniformly mixed at a molar ratio of 1:2.1:5, dibutyl tin dilaurate in an amount of 0.04 times that of isophorone diisocyanate is added, stirring is carried out at 82.5°C and 110 r / min under nitrogen protection for 3.5h, the temperature is lowered to 56.5°C, 2,2-dimethylol propionic acid in an amount of 0.21 times that of isophorone diisocyanate is added, stirring is continued for 25 min, the temperature is lowered to 41°C, triethylamine in an amount of 0.75 times that of 2,2-dimethylol propionic acid is added, stirring is continued for 25 min, the temperature is lowered to room temperature, deionized water is added to adjust the solid content to 40%, stirring is carried out at 2200 r / min for 25 min, and a polyurethane emulsion is prepared; the polyurethane emulsion, sodium chloride and deionized water are mixed at a mass ratio of 1:0.05:3.2 to prepare a water-based polyurethane finishing solution. The remaining steps are the same as those of Example 2.
[0057] Comparative Example 4:
[0058] The preparation method of the anti-wrinkle non-iron fabric of Comparative Example 4 is different from that of Example 2 only in step (3), which is modified as follows: 3-indole formaldehyde and 3-amino-1,5-pentanediol are added to 3-indole formaldehyde in an amount of 16 times that of 3-indole formaldehyde, stirring is carried out at 62.5°C and 250 r / min under nitrogen protection for 5.5h, and indole diol is prepared by drying at 65°C under vacuum for 13h; 3-indole diol, polytetrahydrofuran diol and isophorone diisocyanate are uniformly mixed at a molar ratio of 1:2.1:5, dibutyl tin dilaurate in an amount of 0.04 times that of isophorone diisocyanate is added, stirring is carried out at 82.5°C and 110 r / min under nitrogen protection for 3.5h, the temperature is lowered to 56.5°C, 2,2-dimethylol propionic acid in an amount of 0.21 times that of isophorone diisocyanate is added, stirring is continued for 25 min, the temperature is lowered to 41°C, triethylamine in an amount of 0.75 times that of 2,2-dimethylol propionic acid is added, stirring is continued for 25 min, the temperature is lowered to room temperature, deionized water is added to adjust the solid content to 40%, stirring is carried out at 2200 r / min for 25 min, and a polyurethane emulsion is prepared; the polyurethane emulsion and deionized water are mixed at a mass ratio of 1:3.2 to prepare a water-based polyurethane finishing solution. The remaining steps are the same as those of Example 2.
[0059] Comparative Example 5:
[0060] The preparation method of the anti-wrinkle non-iron fabric of Comparative Example 5 is different from that of Example 2 in that steps (3) and (4) are not performed, and step (2) is modified as follows: the ultraviolet absorber, epichlorohydrin and anhydrous ethanol are mixed uniformly at a mass ratio of 1:1.3:26, a 10% sodium carbonate aqueous solution is used to adjust the pH to 8.5, and an anti-ultraviolet finishing solution is prepared; the flame retardant, triphenylphosphine and anhydrous ethanol are mixed uniformly at a mass ratio of 1:0.06:19, and a flame-retardant finishing solution is prepared; the viscose fabric is placed in the anti-ultraviolet finishing solution, the bath ratio is 1:20, two-dip-two-pad is performed, the wet pick-up rate is 80%, reaction is performed at 55°C for 35 min, washing is performed with deionized water for 5 times, drying is performed at 100°C for 1.5 h, the viscose fabric is immersed in the flame-retardant finishing agent, the bath ratio is 1:30, standing is performed for 25 min, two-dip-two-pad is performed, the wet pick-up rate is 80%, reaction is performed at 73°C for 2.5 h, washing is performed with deionized water for 5 times, drying is performed at 100°C for 1.5 h, and the anti-wrinkle non-iron fabric is prepared. The remaining steps are the same as those of Example 2.
[0061] Test Example 1
[0062] Test of anti-wrinkle performance
[0063] Test method: According to the standard GB / T 3819-1997 “Determination of crease recovery of textile fabrics-recovery angle method”, the anti-wrinkle non-iron fabrics prepared in the examples and comparative examples are tested for recovery angle on a YG541L type digital fabric crease elasticity tester. The results are shown in Table 1.
[0064] Table 1
[0065] Recovery angle (°) Recovery angle (°) Example 1 181 Comparative Example 1 179 Example 2 186 Comparative Example 2 176 Example 3 183 Comparative Example 3 180 Comparative Example 4 178 Comparative Example 5 156
[0066] From the experimental data of Examples 1-3 and Comparative Examples 1-5 in Table 1, it can be found that the anti-wrinkle non-iron fabric prepared by the present application has good anti-wrinkle performance.
[0067] By comparison, the recovery angle of Examples 1-3 is greater than that of Comparative Example 5, indicating that the polyurethane emulsion is prepared by reacting indolyl glycol, polytetrahydrofuran diol, 2,2-dimethylol propionic acid and isophorone diisocyanate, and then reacting with triethylamine. The water-based polyurethane finishing solution is prepared by mixing the polyurethane emulsion with sodium chloride; the viscose fabric is a cellulose fabric with low breaking strength and easy wrinkling; the water-based polyurethane resin has good chemical stability, small pollution and convenient use, and has good film-forming property and elasticity, and can be used for anti-wrinkle finishing of viscose fabric, can rely on its own resilience to drive the resilience of viscose fabric, and improve the anti-wrinkle performance of viscose fabric.
[0068] Test Example 2
[0069] Test of flame retardant performance
[0070] Test method: The limiting oxygen index of the examples and the comparative examples was tested according to the standard GB / T 5454-1997 "Textile Burning Performance Test Oxygen Index Method". The results are shown in Table 2.
[0071] Table 2
[0072] Limiting oxygen index (%) Limiting oxygen index (%) Example 1 32.19 Comparative Example 1 31.47 Example 2 33.47 Comparative Example 2 22.18 Example 3 32.64 Comparative Example 3 31.51 Comparative Example 4 31.62 Comparative Example 5 32.57
[0073] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-5 in Table 2, it can be found that the wrinkle-resistant and non-iron fabric prepared by the present application has good flame retardant performance.
[0074] Through comparison, the limiting oxygen index of Examples 1-3 is greater than that of Comparative Example 2, indicating that a phosphorus-nitrogen synergistic flame retardant is synthesized by reacting cyanuric chloride and [(4-aminophenyl)methylene] diphosphonic acid, and the phosphonic groups on the flame retardant can undergo ring-opening reaction with the epoxy groups introduced on the viscose fabric under the action of the catalyst, thereby grafting the flame retardant on the viscose fabric and improving the flame retardant performance of the wrinkle-resistant and non-iron fabric.
[0075] Test Example 3
[0076] Test of Anti-ultraviolet Performance
[0077] Test method: The UPF value of the examples and the comparative examples was determined according to GB / T 18830-2009 "Evaluation of Anti-ultraviolet Performance of Textiles". The results are shown in Table 3.
[0078] Table 3
[0079]
[0080]
[0081] From the comparison of the experimental data of Examples 1-3 and Comparative Examples 1-5 in Table 2, it can be found that the wrinkle-resistant and non-iron fabric prepared by the present application has good anti-ultraviolet performance.
[0082] Through comparison, the UPF value of Examples 1-3 is greater than that of Comparative Example 1, indicating that the ultraviolet absorber is prepared by reacting 4-(2-chloroethyl)benzaldehyde and 3,5-difluorophenylacetonitrile, and chlorine atoms are introduced on the ultraviolet absorber; the chlorine atoms on the ultraviolet absorber and the epoxy chloropropane can undergo substitution reaction with the hydroxyl groups on the viscose fabric, thereby grafting the ultraviolet absorber and the epoxy groups on the viscose fabric; the ultraviolet absorber grafted on the viscose fabric contains a diphenyl acrylonitrile structure, and the diphenyl acrylonitrile structure can undergo cis-trans isomerization under ultraviolet light, changing from Z configuration to E configuration. This isomerization is reversible, and the Z configuration can be restored after the ultraviolet light is removed. The reversible cis-trans isomerization can absorb ultraviolet light energy and convert it into chemical energy, thereby improving the anti-ultraviolet performance of the wrinkle-resistant and non-iron fabric.
[0083] By comparison, the UPF value of examples 1-3 is greater than that of comparative examples 3 and 5, which indicates that the indolyl glycol is prepared by reacting 3-indole formaldehyde and 3-amino-1,5-pentanediol; the polyurethane emulsion is prepared by reacting the indolyl glycol, polytetrahydrofuran diol, 2,2-dimethylol propionic acid, isophorone diisocyanate, and triethylamine; the water-based polyurethane finishing liquid is prepared by mixing the polyurethane emulsion and sodium chloride; the indolyl group introduced into the polyurethane main chain contains a conjugated aromatic structure, which can absorb ultraviolet light through the transition of π electrons, thereby further improving the anti-ultraviolet performance of the wrinkle-resistant and non-iron fabric.
[0084] Test Example 4
[0085] Tensile test
[0086] Test method: GB / T3923.1-2013, according to "Textiles - Determination of tensile properties of fabrics - Part 1: determination of breaking force and elongation at break (strip method)", the radial breaking strength of examples and comparative examples is tested, the tensile rate is 100 r / min, and the gauge length is 200 mm. The results are shown in Table 4.
[0087] Table 4
[0088] Breaking strength (N) Breaking strength (N) Example 1 578.9 Comparative Example 1 578.3 Example 2 581.2 Comparative Example 2 576.7 Example 3 580.6 Comparative Example 3 563.8 Comparative Example 4 561.1 Comparative Example 5 545.9
[0089] From the experimental data comparison of examples 1-3 and comparative examples 1-5 in Table 4, it can be found that the wrinkle-resistant and non-iron fabric prepared by the present application has good tensile performance.
[0090] By comparison, the breaking strength of examples 1-3 is greater than that of comparative examples 3-5, which indicates that the indolyl glycol is prepared by reacting 3-indole formaldehyde and 3-amino-1,5-pentanediol; the polyurethane emulsion is prepared by reacting the indolyl glycol, polytetrahydrofuran diol, 2,2-dimethylol propionic acid, isophorone diisocyanate, and triethylamine; the water-based polyurethane finishing liquid is prepared by mixing the polyurethane emulsion and sodium chloride; the indolyl group can form a cation-π supramolecular interaction with sodium ions to form a "point-to-plane" non-covalent bond, thereby forming a cross-linked network between the polyurethane molecular chains; viscose fabric is a cellulose fabric, and the main reason for the breaking of viscose fibers is the slippage of molecular chains, and the cross-linking effect can enhance the binding force between molecular chains and inhibit the slippage phenomenon, thereby improving the tensile performance of the wrinkle-resistant and non-iron fabric; at the same time, the excellent tensile performance of polyurethane can further improve the tensile performance of viscose fabric.
[0091] The above detailed description of the specific embodiments of the present application has been given to understand the purpose, technical solutions and beneficial effects of the present application. It should be understood that the above description is only a specific embodiment of the present application and is not used to limit the protection scope of the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. An anti-crease non-iron fabric, characterized by, The anti-wrinkle non-iron fabric is prepared by reacting viscose fabric with an ultraviolet absorber and epichlorohydrin, then with a flame retardant to obtain a pre-modified fabric; reacting indole glycol, polytetrahydrofuran diol and 2,2-dimethylol propionic acid with isophorone diisocyanate, then with triethylamine to obtain a polyurethane emulsion; preparing a water-based polyurethane finishing liquid by mixing the polyurethane emulsion with sodium chloride; and reacting the pre-modified fabric with the water-based polyurethane finishing liquid to obtain the anti-wrinkle non-iron fabric. The ultraviolet absorber is prepared by reacting 4-(2-chloroethyl)benzaldehyde and 3,5-difluoroacetonitrile. The flame retardant is prepared by reacting cyanuric chloride and [(4-aminophenyl)methylene]diphosphonic acid. The indole glycol is prepared by reacting 3-indole formaldehyde and 3-amino-1,5-pentanediol.
2. A process for the preparation of an anti-crease non-iron fabric characterized in that, The preparation method of the anti-wrinkle non-iron fabric comprises the following steps: (1) placing the viscose fabric in an ultraviolet-resistant finishing liquid, with a bath ratio of 1:20, double-dipping and double-rolling, a liquid retention rate of 80%, reacting at 50-60 DEG C for 30-40 min, washing and drying, then immersing in a flame-retardant finishing agent, with a bath ratio of 1:30, standing for 20-30 min, double-dipping and double-rolling, a liquid retention rate of 80%, reacting at 70-76 DEG C for 2-3 h, washing and drying to obtain the pre-modified fabric; (2) mixing indole glycol, polytetrahydrofuran diol and isophorone diisocyanate in a molar ratio of 1:(2-2.2):(4.8-5.2), adding dibutyltin dilaurate in an amount of 0.03-0.05 times the mass of isophorone diisocyanate, reacting at 80-85 DEG C for 3-4 h under nitrogen protection, cooling to 55-58 DEG C, adding 2,2-dimethylol propionic acid in an amount of 0.2-0.22 times the molar amount of isophorone diisocyanate, reacting for 20-30 min, cooling to 40-42 DEG C, adding triethylamine in an amount of 0.7-0.8 times the mass of 2,2-dimethylol propionic acid, reacting for 20-30 min, cooling to room temperature, adding deionized water to adjust the solid content to 40%, stirring at 2000-2400 r / min for 20-30 min to obtain the polyurethane emulsion; mixing the polyurethane emulsion, sodium chloride and deionized water in a mass ratio of 1:(0.04-0.06):(3-3.4) to prepare the water-based polyurethane finishing liquid; (3) immersing the pre-modified fabric in the water-based polyurethane finishing liquid, with a bath ratio of 1:30, double-dipping and double-rolling at room temperature, a liquid retention rate of 80%, pre-baking at 80 DEG C for 3-5 min, heating to 150 DEG C, baking for 4-6 min, washing and drying to obtain the anti-wrinkle non-iron fabric.
3. The method for preparing a wrinkle-resistant and non-ironing fabric according to claim 2, characterized in that: The face density of the viscose fabric of step (1) is 250 g / m 2 .
4. The method for preparing a wrinkle-resistant and non-ironing fabric according to claim 2, wherein: In step (1), the anti-ultraviolet finishing liquid is prepared by mixing the ultraviolet absorber, epichlorohydrin and anhydrous ethanol in a mass ratio of 1:(1.2-1.4):(25-27), adjusting the pH to 8-9 with a sodium carbonate aqueous solution, and preparing the anti-ultraviolet finishing liquid.
5. The method for preparing a wrinkle-resistant and non-ironing fabric according to claim 4, characterized in that: The preparation method of the ultraviolet absorber is as follows: sodium hydroxide and anhydrous ethanol are uniformly mixed at a mass ratio of 1:(90-100) to prepare a sodium hydroxide alcohol solution; 4-(2-chloroethyl)benzaldehyde and 3,5-difluorophenylacetonitrile are added to the sodium hydroxide alcohol solution in a molar ratio of 1:1, and the mixture is stirred at 30-40 DEG C and 200-300 r / min for 3-4 h, and then dried at 50-60 DEG C under vacuum for 8-10 h to obtain the ultraviolet absorber.
6. The method of making an anti-crease non-iron fabric according to claim 4, wherein, The mass fraction of the sodium carbonate aqueous solution is 10%.
7. The method for preparing a wrinkle-resistant and non-ironing fabric according to claim 2, characterized in that: The preparation method of the flame-retardant finishing liquid in step (1) is as follows: a flame retardant, triphenylphosphine and anhydrous ethanol are uniformly mixed at a mass ratio of 1:(0.05-0.07):(18-20) to prepare the flame-retardant finishing liquid.
8. The method for preparing a wrinkle-resistant and non-ironing fabric according to claim 7, characterized in that: The preparation method of the flame retardant is as follows: cyanuric chloride and [(4-aminophenyl)methylene]diphosphonic acid are added to toluene in a molar ratio of 1:3, and then 0.04-0.06 times the mass of cyanuric chloride is added to the mixture as triethylamine, and the mixture is stirred at 50-60 DEG C and 300-500 r / min for 4-5 h, and then dried at 70-80 DEG C under vacuum for 10-12 h to obtain the flame retardant.
9. The method for preparing a wrinkle-resistant and non-ironing fabric according to claim 2, characterized in that: The model of the polytetrahydrofuran glycol in step (2) is PTMG2000.
10. The method of making an anti-crease non-iron fabric according to claim 2, wherein, The preparation method of the indolyl glycol in step (2) is as follows: 3-indole formaldehyde and 3-amino-1,5-pentanediol are added to tetrahydrofuran in a molar ratio of 1:1, and the mixture is stirred at 60-65 DEG C and 200-300 r / min for 5-6 h under nitrogen protection, and then dried at 60-70 DEG C under vacuum for 12-14 h to obtain the indolyl glycol.